2018
DOI: 10.1038/s41598-018-34994-4
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for mitigation of coral bleaching by manganese

Abstract: Unprecedented mass coral bleaching events due to global warming and overall seawater pollution have been observed worldwide over the last decades. Although metals are often considered as toxic substances for corals, some are essential at nanomolar concentrations for physiological processes such as photosynthesis and antioxidant defenses. This study was designed to elucidate, the individual and combined effects of nanomolar seawater enrichment in manganese (Mn) and iron (Fe), on the main physiological traits of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 75 publications
11
32
0
Order By: Relevance
“…Although phytoplankton are eaten by zooplankton, which in turn are eaten by T. coccinea, corals prefer oligotrophic waters, where primary productivity is low (Sheppard et al 2017;Martin 2018). Also, iron enrichment can lead to impaired calcification and significant bleaching in corals (Biscéré et al 2018). These factors might explain T. coccinea's presence being associated with low minimum iron levels.…”
Section: Discussionmentioning
confidence: 99%
“…Although phytoplankton are eaten by zooplankton, which in turn are eaten by T. coccinea, corals prefer oligotrophic waters, where primary productivity is low (Sheppard et al 2017;Martin 2018). Also, iron enrichment can lead to impaired calcification and significant bleaching in corals (Biscéré et al 2018). These factors might explain T. coccinea's presence being associated with low minimum iron levels.…”
Section: Discussionmentioning
confidence: 99%
“…Over three decades of experiments and observations have developed and refined the central bleaching paradigm (e.g., Cziesielski et al, ) whereby accumulation of reactive oxygen species (ROS), and/or reactive nitrogen species (RNS), leads to signaling cascades and in turn expulsion or xenophagy of the algal endosymbionts (Family: Symbiodiniaceae) from the coral host (Davy et al, ; Smith et al, ; Tchernov et al, ; Weis, ). An overwhelming body of evidence has repeatedly demonstrated that perturbations to environmental factors underpinning optimum metabolic functioning can all result in bleaching; notably, temperature (Levin et al, ; Tchernov et al, ; Tolleter et al, ), light (Downs et al, ; Lesser & Farrell, ), salinity (Aquilar et al, 2019; Gardner et al, ; Ochsenkühn, Röthig, D'Angelo, Wiedenmann, & Voolstra, ) as well as inorganic nutrients including CO 2 (Anthony, Kline, Diaz‐Pulido, Dove, & Hoegh‐Guldberg, ; Crawley et al, ), iron and other trace metals (Biscéré, Ferrier‐Pagès, Gilbert, Pichler, & Houlbrèque, ; Ferrier‐Pagès et al, ; Shick et al, ), and the nitrogen‐to‐phosphate ratio (Fabricius, Cséke, Humphrey, & De'ath, ; Pogoreutz et al, ; Wiedenmann et al, ). Stability of the symbiosis rests on fine‐tuned resource exchange of primary metabolic currencies—C, N, P, electron carriers, etc.—among the algal symbionts, host, and/or broader associated microbiome (Suggett, Warner, & Leggat, ).…”
Section: The Mechanistic Biological Network Underpinning Bleaching Sementioning
confidence: 99%
“…In this regard, an increased bleaching susceptibility of scleractinian corals has been observed when subjected to the combined effects of thermal stress and copper or nickel enrichment (Biscéré et al, 2017;Fonseca et al, 2017;Banc-Prandi and Fine, 2019). Also, iron enrichment has been shown to impair calcification and induce significant bleaching (Wells et al, 2011;Biscéré et al, 2018). On the contrary, manganese enrichment may alleviate the deleterious effect of heat stress on corals, by enhancing chlorophyll concentrations, photosynthetic efficiency, and gross photosynthetic rates at ambient and elevated temperature (Biscéré et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Also, iron enrichment has been shown to impair calcification and induce significant bleaching (Wells et al, 2011;Biscéré et al, 2018). On the contrary, manganese enrichment may alleviate the deleterious effect of heat stress on corals, by enhancing chlorophyll concentrations, photosynthetic efficiency, and gross photosynthetic rates at ambient and elevated temperature (Biscéré et al, 2018). All together, these studies suggest that the effects of metals on coral physiology are metal and concentration-dependent, and that interactions between metals also exist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation